2004
DOI: 10.1258/002221504772784667
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular neurilemmoma; a diagnostic dilemma

Abstract: Neurilemmomas are slow growing, benign neoplasms of neural crest Schwann cell origin. They arise from any peripheral, spinal or cranial nerve except the olfactory and optic. Presentation is usually asymptomatic but focal neurological signs and symptoms may be associated with nerve compression. With approximately one third of all documented cases presenting in the head and neck region, we report a case of a submandibular neurilemmoma misdiagnosed pre-operatively. The diagnostic difficulties are discussed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Sometimes, the imaging appears features of benign tumor, the histological features also show the morphology of schwannoma, so both the imaging and histology show benign tumor features [12]. However, although with advanced imaging techniques even with fine needle biopsy, sometimes schwannoma still will be misdiagnosed pre-operatively [13]. Because of the rarity of these intraosseous schwannoma, it is important that the diagnosis is made pre-operatively by the pathologist examining the needle biopsies and the radiologist interpreting the scans.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the imaging appears features of benign tumor, the histological features also show the morphology of schwannoma, so both the imaging and histology show benign tumor features [12]. However, although with advanced imaging techniques even with fine needle biopsy, sometimes schwannoma still will be misdiagnosed pre-operatively [13]. Because of the rarity of these intraosseous schwannoma, it is important that the diagnosis is made pre-operatively by the pathologist examining the needle biopsies and the radiologist interpreting the scans.…”
Section: Discussionmentioning
confidence: 99%
“…Almeyda et al . [37] reported a case of submandibular schwannoma (3.5 cm × 2 cm × 2 cm) misdiagnosed preoperatively. The differential diagnosis of adenolymphoma (Warthin’s tumor) was based on the clinical examination, ultrasound and two fine needle aspirations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on operative findings, the mass was thought to be a tumor derived from the lingual nerve. Almeyda et al 37 reported a case of submandibular schwannoma (3.5 x 2 x 2 cm) misdiagnosed pre-operatively. The differential diagnosis of adenolymphoma (Warthin's tumor) was based on the clinical examination, US and two fine needle aspirations.…”
Section: Discussionmentioning
confidence: 99%
“…Even with advances in imaging, the diagnostic dilemma remains. 37 MRI has been of greater use, with a distinctive target pattern demonstrated by most, but not all schwannomas. 38 In the case presented by Asaumi et al 39 the US, CT, and MRI appearance of schwannoma of the upper lip (3.8 x 1.8 x 1.4 cm) correlated well with the histologic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation